Rehabilitation Research in Denmark Between 2001 and 2020: A Scoping Review - Momsen, Anne-Mette Hedeager; Fox, Jasmine Charlotte; Nielsen, Claus Vinther; Thuesen, Jette; Maribo, Thomas (Frontiers in Rehabilitation Sciences, 2022)
Abstract The demand for rehabilitation has increased, and evidence is rapidly growing, however, the rehabilitative health strategy receives less attention than treatment. Knowledge of what is being researched, who the target groups are and who contributes to rehabilitation research is deficient. We did not find any reviews mapping rehabilitation research regarding the research questions. The objective was to identify and synthesize existing scientific evidence on rehabilitation research published by Danish institutions between 2001-2021. The research questions to be explored were: Among which study groups has rehabilitation research been published? Which types of studies on rehabilitation have been published? Which institutions have been involved in rehabilitation research? Methods The process was guided according to the Joanna Briggs Institute’s scoping review methodology. Four databases were searched. All types of peer-reviewed studies on any target group and rehabilitation setting, with any affiliation to a Danish institution were eligible to be included. Studies were categorized referring to population and type of design. Institutions were counted as Danish first authorship. Results The search revealed 3100 studies, following screening 1779 were included. 24 broad study groups were identified, mostly diagnose-based health conditions. Musculoskeletal, cancer, and cardiac had 342, 228, and 174 studies respectively. 1545 had a Danish first authorship, most of the Danish publications came from hospitals (56.6%) and universities (28.4%). The publication trend showed an almost linear development, with 10-15% increase during the period. Conclusions Following screening 1779 studies were included involving 24 broad study groups. Most categories were diagnose-based; musculoskeletal, cancer and cardiac health conditions encompassed most studies. All study designs were represented, 1/10 were secondary studies. The majority (87%) of studies had a Danish first authorship. The majority of first affiliations were among hospitals followed by universities. A few municipalities were presented, although they are yet to have research responsibility. Publication trends showed an increase, primarily from 2013. Database registration: Open Science Framework: DOI 10.17605/OSF.IO/2AENX